Effects of Teachers’ Interpersonal Conflicts on Their Motivation at Sec-ondary Level in Gilgit - Anwar Ul Haq; Syed Ghazanfer Abbas; Usama Bashir (Jurnal Multidisiplin Madani, 2023)
The study was aimed to explore the teachers’ interpersonal conflicts and their motivation level. It also intended to determine the relationship and effects of teachers’ interpersonal conflicts on their motivation. The study was descriptive type of research and carried out in a quantitative manner. Population of the study encompasses all the teachers of the public sector lower secondary schools in Gilgit. There were 150 teachers appointed in 12 secondary schools. Random sampling technique was used and 100 teachers were randomly selected from the population for the study. A comprehensive questionnaire was developed for the teachers to explore the teachers’ interpersonal conflicts, motivation and their relationship. The questionnaire comprised two scales, one was conflict assessment scale and the second was motivation assessment scale. The data was collected by the personal visit of researcher and finally analyzed and tabulated by using SPSS 16th edition. Statistical operations like Cronbach’s Alpha Reliability, Correlation, and Regression analysis were used to analyze the data and find the results of intended objectives. The interpreted data shows that the majority of respondents which is 64% of total sample population were found in an average level. The collected teachers’ opinions explored that there are interpersonal conflicts which they are facing with their fellow workers, supervisors, students, and parents of teachers. The second finding of study was the motivation of teachers. The opinion given on the questionnaire by the teachers show that the majority of respondents have high motivation level. The last and main finding of the study explores the effects of teachers’ interpersonal conflicts on the motivation of teachers. The statistical measurements determine that there is a relationship among the interpersonal conflict and motivation of teachers and these conflicts affect their motivation level. The effects of conflicts on the motivation measured through regression were 8.1%. While this effect was significant at 0.01 level of significance (β= -0.26, t= -2.93). So, to decimate this effect it’s quite necessary for the organizations and institutions to take precautionary steps prior to the occurrence of conflicts and overcome the communication gaps. Awareness sessions and seminars may have positive indicators for the prevention of conflicts